Love and Method. Lessons and Example of Arendtian Tradition - Jonutytė, Jurga (Tautosakos darbai, 2025)
Maria Tamboukou, Epistolary Narratives of Love, Gender and Agonistic Politics. An Arendtian Approach, London, New York: Routledge, 2024, 182 p., ISBN 978-1032208428